Effect of laminated parameters on mechanical properties hybrid juteramie reinforced unsaturated polyester composite - Mohammad Hazim, Mohamad Hamdan (2021)
The natural fibre is an alternative to synthetic fibre. It is key to saving money, conserving natural resources, and providing a lightweight structure. The work on hybridising natural fabrics is still in its infancy. The current research investigates the mechanical properties of reinforced unsaturated polyester resin with various parameter types such as layering size, layering length, and fabric orientation. In the current study, the impact of excessive moisture on mechanical properties for hybrid jute-ramie reinforced UPE composites is also investigated. For experimental purposes, the properties for single fibre, yam fibre and fabric properties were analysed and registered. The simple Ill woven jute and ramie were defined in chemical composition, physical properties and mechanical properties. TAPPI 203 OM 02, Fourier Transform Infra-Red (FTIR) method, thermogravimetric analysis (TGA) and thermogravimetric derivative (DTG) to assess the chemical composition and thermal stability of woven jute and ramie. It is essential to note the mechanical performance for single yam fibre and woven fabric in a different warp and weft direction. Thus, the multi-fibre-pull-out test, grab test, tearing and puncture test was used to record the performance of yam fibre and woven fabric of jute and ramie. The scanning electron microscope was employed to examine fracturen faces, damage (splitting, matrix cracking, delamination) and composite surface morphology. The composite sample fabricated via hand lay-up and hydraulic compression technique. Maximum 4 layers of layering size were applied with layering sequence and fabric orientation. Four fabric configuration types have been analysed: 0° laminates, cross-ply laminates, angle-ply laminates and quasi-isotropic. According to the American Society for Testing Materials (ASTM), all-composite samples undergo tensile testing, flexural testing, and impact testing according to the American Society for Testing Materials (ASTM). The composite material with 2 and 3 layers immersed in distilled water for about 30 days in the water absorption and thickness swelling testing. The present study indicated that the mechanical properties of UPE could considerably be improved by incorporating different layering sizes of jute and ramie reinforcement. The mechanical properties for hybrid composite lie in between single jute composite and single ramie composite. Based on the results have shown that the effect of stacking sequence dominance in the flexural test. On the other hand, the composite with fabric orientation of 0° laminates and cross-ply found to be significant on the tensile testing. Overall, the vital parameter for tensile properties is the following: l) layering size 2) fabric orientation 3) layering sequence. Nonetheless, following such pattern are recognised for flexural and impact: I) layering size 2) layering sequence 3) fabric orientation. Other than that, the tensile composite's fracture surface was further investigated via scanning electron microscopic (SEM). According to the SE:vl image, it can be concluded that the fracture surface is dependent on fabric orientation. The composites with fabric orientations of angle-ply and quasi-isotropic have a smooth fracture surface. Their presence of microvoid and porous on the surface is minimum. Single jute, single ramie and hybrid juteramie were compared with computational models such as rule of mixture, inverse rule of mixture, Halpin-Tsai, Hirsch and Cox- Krencel's. Meanwhile, another study revealed that the hybrid jute-ramie mechanical properties reinforced UPE dropped when exposed to excessive moisture. Mechanism ofwatcr transport for the composite sample follow nonfickian behaviour. Finally, the rate of water absorption found to increase due to the higher number of layering sizes.